2004
DOI: 10.1023/b:scie.0000018528.59913.48
|View full text |Cite
|
Sign up to set email alerts
|

Tracing knowledge diffusion

Abstract: Knowledge diffusion is the adaptation of knowledge in a broad range of scientific and engineering research and development. Tracing knowledge diffusion between science and technology is a challenging issue due to the complexity of identifying emerging patterns in a diverse range of possible processes. In this article, we describe an approach that combines complex network theory, network visualization, and patent citation analysis in order to improve the means for the study of knowledge diffusion. In particular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
78
0
2

Year Published

2006
2006
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(82 citation statements)
references
References 31 publications
2
78
0
2
Order By: Relevance
“…Power law citation distributions were also found on an extensive US patents database granted between January 1963 and December 1999. While analyzing only citations of papers in US patents, Chen and Hicks [329] concluded that papers with explicit funding acknowledgements tended to be cited relatively more often than papers without explicit acknowledgements, possibly because those articles in the former category are more likely to have impact on inventions described by patents.…”
Section: Citationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Power law citation distributions were also found on an extensive US patents database granted between January 1963 and December 1999. While analyzing only citations of papers in US patents, Chen and Hicks [329] concluded that papers with explicit funding acknowledgements tended to be cited relatively more often than papers without explicit acknowledgements, possibly because those articles in the former category are more likely to have impact on inventions described by patents.…”
Section: Citationsmentioning
confidence: 99%
“…Most importantly, there is an apparent universal behavior at the two rightmost classes, corresponding to journals of limited and unlimited number of pages per paper [328]. In contrast, patent-to-patent citations present a power law [329].…”
Section: Citationsmentioning
confidence: 99%
“…Some of these studies utilize patent citations to measure local knowledge flows [JAFFE & AL., 1993;ALMEIDA & KOGUT, 1999;SINGH, 2005]. The patent citations to academic research are also used as a measure of the relation between science and technology [SORENSON & FLEMING, 2004;CHEN & HICKS, 2004].…”
mentioning
confidence: 99%
“…Secondly, a growing number of literature is focused on the importance of social networks as pathways that channel the flow of knowledge among actors (Jaffe and Trajtenberg 1996;Borner et al 2006;Granovetter 1973;Hansen 1999;Singh 2005;Sorenson et al 2006;Waguespack and Birnir 2005), indicating that knowledge flows are stronger within than between regions or firms (Singh 2005). A third branch investigates the important implications of knowledge diffusion for public policy and economic growth (Chen and Hicks 2004;Grossman and Helpman 1991;Huang et al 2005;Karki 1997;Romer 1990;Singh 2007). Researchers on these topics find that understanding the institutional, geographic, and temporal dimensions of the spread of newly created knowledge is crucial for policy-making purposes (Jaffe and Trajtenberg 1996).…”
Section: Introductionmentioning
confidence: 99%